PELUANG GANTI PEKERJAAN MIGRAN PEREMPUAN DI KOTA DENPASAR - Made Ika Prastyadewi; Putu Yusi Pramandari; Gde Bayu Surya Parwita (STIMI Handayani Denpasar, 2016)
The aim of this study was to determine the effect of education level, age, andmarital status against the odds change jobs women migrans in the city of Denpasar.The study was conducted in four districts in the city of Denpasar. Respondents arenon-permanent migran women in Denpasar where the sample is determined usingthe quota by the number of samples is 120 people. Analysis of the data used toachieve the goal is through the analysis of Binary Logistic technique. Based on theresults of the analysis and discussion, it can be concluded that the level of education,age, and marital status significantly influence migran women’s chances of changingjobs in Denpasar. Partially, education level and employment status positive influenceon changing employment opportunities migran women in the city of Denpasar. Whileage does not significantly influence the chances of changing jobs migran women inthe city of Denpasar.